Bridging Marginalities: Assessing the Effects of HIV/AIDS Prevention Initiatives on Rural Zimbabwean Female Sex Workers - Rushambwa, Ruramai; Mugambiwa, Shingirai (Indonesian Journal of Social Research (IJSR), 2025)
This study aimed to assess the efficacy of HIV/AIDS preventive initiatives specifically designed for female sex workers in Silobela, Zimbabwe. The study employed a phenomenological research approach, with intersectionality theory as its theoretical framework. Due to the delicate nature of the topic, participants were selected using a snowball sampling method. Data collection for this study involved unstructured face-to-face interviews with Female Sex Workers and Key Informant Interviews (KII), with a sample size of twelve participants. The findings were analyzed using theme analysis and revealed that Female sex workers (FSWs) in Silobela have demonstrated a keen interest in the HIV/AIDS preventative actions and initiatives done by various partners. The individuals often experienced disenchantment with these programs due to the humiliation they encountered, which resulted from stigma and rejection from both society and medical professionals. The paper proposes several measures to tackle these concerns, including raising awareness among the public about the nature of sex work and promoting reverence for individuals involved in it. These actions are expected to enhance the effectiveness of HIV/AIDS prevention programs targeting female sex workers (FSWs) in Silobela.